Modern Tools and Techniques for precise nitrogen fertilizer management - Goswami, Rakesh Giri; Kumar, Thaneshwar; Singh, Ashish Kumar; Bajpai, R K (Indian Farming, 2017)
Urea and other nitrogenous fertilizers are the need of the hour due to increased population and nutritional demand, but not at the cost of environmental health and life of living organisms. The blind use of urea is only due to lack of scientific knowledge, poor management practices and illiteracy among farmers. Hence for sustainable livelihood of future generations and for reduction of money spent on import of fertilizers; adapting modern tools like Nutrient Expert, NDVI sensor and leaf colour chart are required for proper management of fertilizers.